Effect of Cyclic Mechanical Stimulation on the Expression of Osteogenesis Genes in Human Intraoral Mesenchymal Stromal and Progenitor Cells. (7th April 2014) - Lohberger, Birgit; Kaltenegger, Heike; Stuendl, Nicole; Payer, Michael; Rinner, Beate; Leithner, Andreas
Abstract : We evaluated the effects of mechanical stimulation on the osteogenic differentiation of human intraoral mesenchymal stem and progenitor cells (MSPCs) using the Flexcell FX5K Tension System that mediated cyclic tensile stretch on the cells. MSPCs were isolated from human mandibular retromolar bones and characterized using flow cytometry. The positive expression of CD73, CD90, and CD105 and negativity for CD14, CD19, CD34, CD45, and HLA-DR confirmed the MSPC phenotype. Mean MSPC doubling time was 30.4 ± 2.1 hrs. The percentage of lactate dehydrogenase (LDH) release showed no significant difference between the mechanically stimulated groups and the unstimulated controls. Reverse transcription quantitative real-time PCR revealed that 10% continuous cyclic strain (0.5 Hz) for 7 and 14 days induced a significant increase in the mRNA expression of the osteogenesis-specific markers type-I collagen (Col1A1), osteonectin (SPARC), bone morphogenetic protein 2 (BMP2), osteopontin (SPP1), and osteocalcin (BGLAP) in osteogenic differentiated MSPCs. Furthermore, mechanically stimulated groups produced significantly higher amounts of calcium deposited into the cultures and alkaline phosphatase (ALP). These results will contribute to a better understanding of strain-induced bone remodelling and will form the basis for the correct choice of applied force in oral and maxillofacial surgery.